Imprint '76 - Heller, Jules (Toronto : The Print and Drawing Council of Canada, 1976)
Allen, George ; Bain, Freda Guttman ; Bartram, Edward ; Bowden, Gary ; Cagnon, Liz ; Cowin, Jack ; Crockett, David ; Evergon ; Evermon, Bob ; Hawken, George ; Hornell, Taffy ; Johnston, Barbara ; Lobchuk, Bill ; Matsubara, Naoko ; May, Margaret ; Metcalfe, Eric W. ; Mosna, Tony ; Nash, Susan ; Noestheden, John ; Oberheide, Heide ; Ouchi, Eugene ; Parsons, Bruce ; Pelzer, Craig ; Sawai, Noboru ; Sheckter, Bonnie ; Tétreault, Pierre-Léon ; Tookoome ; Whittome, Irene ; Woods, W. Chris ; Zeigler-Sungur, Barbara
Frans & Engels
Imprint '76, Itinerary: Saidye Bronfman Centre of the YM - YWHA & NHS, Montréal, June 29, 1976 to August 8, 1976 ; McIntosh Art Gallery, the University of Western Ontario, London, Ontario, September 8, 1976 to October 3, 1976 ; The Art Gallery of Ontario/Musée des Beaux-Arts de l'Ontario, Toronto, October 16, 1976 to November 28, 1976 ; Woodstock Public Library and Art Gallery, Woodstock, Ontario, December 1976 ; Kitchener-Waterloo Art Gallery, Kitchener, Ontario, February 1977 ; etc.
boek